Oxytocin and the Biopsychology of Performance in Team Sports. (10th September 2012) - Pepping, Gert-Jan; Timmermans, Erik J.
Abstract : Little is known about the biopsychological underpinnings of expert performance in team sports. In this paper we show that there is a vast support for oxytocin as a neuropeptide involved in the encouragement of important processes linked to greater team performance in sport. We argue that oxytocin is related to biopsychological processes aimed at convergence of emotions and moods between people, and in doing so it is a critical neuropeptide involved in the shaping of important team processes in sport such as trust, generosity, altruism, cohesion, cooperation, and social motivation, and also envy and gloating. Future research should examine the role of oxytocin in these essential components of sport performance. In particular, the link between oxytocin, emotional contagion and the cultivation of experiences of positive emotions is a worthwhile line of investigation for sport participation and development as well as high performance in sport.